Knockout of cyclin B1 in granulosa cells causes female subfertility. Issue 17 (2nd September 2022) - Cheng, Jinmei; Liu, Yixun
ABSTRACT: In mammalian cells, cyclin B1 plays a pivotal role in mitotic and meiotic progression. It has been reported that infertility occurs after disruption of cyclin B1 ( Ccnb1 ) in male germ cells and oocytes. However, it remains to be elucidated whether the specific disruption of Ccnb1 in granulosa cells influences the reproductive activity of female mice. Amhr2 is expressed in granulosa cells (GCs) of the ovary. Here, we mated Ccnb1 Flox/Flox mice with a transgenic mouse strain expressing Amhr2-Cre to generate GC-specific Ccnb1 knockout mice. The results showed that Ccnb1 Flox/Flox, Amhr2-Cre ( Ccnb1 cKO) mice were subfertile but had normal oocyte meiotic progress, spindle shape and protein levels of cohesin subunits REC8 and SMC3 on arm chromosomes during meiosis I. A further study found that 32.4% of oocytes from Ccnb1 cKO mice exhibited chromosome condensation and spindle disassembly after the first polar body extrusion and failed to undergo second meiosis, which was never found in oocytes from Ccnb1 Flox/Flox mice. In addition, the percentages of 2-cell embryos, morulas, and blastocysts in the Ccnb1 mutant group were all dramatically decreased compared to those in the Ccnb1 Flox/Flox group (39.2% vs . 86.8%, 26.0% vs . 85.0%, 19.1% vs . 85.8%, respectively). Therefore, GC-specific Ccnb1 deletion in mice could cause fewer and poor-quality blastocysts and subsequent subfertility, which plays an important role in understanding the function of cyclin B1 in reproduction.